Factors affecting the Consumer Brand Choice Preference towards New Package of Cellular Phone: A Study on Comilla Region - Sultana , Sarmin (Global Disclosure of Economics and Business, 2015)
The aim of the study is to identify the factors that affect consumer brand preference and choice towards a new package of a cellular phone and also to identify the factors that influence the acceptability and attractiveness of a new mobile phone package.  To achieve the objectives of the study a survey has been conducted on 80 respondents in the different area of Comilla. "Multiple Regression Analysis" and "Discriminant Analysis" was made to find out the objectives of the study. The result indicates that there are some factors that affect the customers brand preference on new package of cell phone such as Sim price, Call Rate, Network Coverage, F & F numbers, F & F call rate, Bonus talk time, SMS charge, free internet browsing, after sales service, etc. Consumers in Comilla region are not highly satisfied by using existing brands. It is also find that rural respondents are mainly using low price and simple functions cell phone. So they want new package that will gratify their needs by providing some attributes. Based on the findings, some recommendations have suggested for future action.